Benefits of MPP tracking PV system using perturb and observe technique with boost converter - Russul H. Mohammed; Ali Abdulwahhab Abdulrazzaq; Waleed Khalid Al-Azzawi (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
In recent decades, researchers have become interested in the photovoltaic (PV) system as one of the renewable energies. There are nonlinear I-V and P-V features in the PV generators. The greatest power generated varies with temperature and irradiation. To increase PV power, it is necessary to watch MPP carefully. In order to avoid some of shortcomings of conventional perturb & observe (P&O) MPP tracking approach and increase the transient responsiveness and decrease oscillations of steady-state terminal voltage, this study introduces a modified (P&O) MPPT algorithm employing fuzzy logic-based variable step size. An indoor simulated PV source built from a typical solar panel, DC power supplying, a DC-DC converter, in addition to P&O-based MPPT controlling unit was used to create and test the suggested MPPT algorithm. To demonstrate the P&O strategy's performance benefits under both constant and fluctuating irradiations and temperatures, their simulation under unsteady state circumstances is already performed with MATLAB/Simulink. Results of the simulations demonstrate that the photovoltaic simulation system can precisely monitor the highest power point. According to the simulation findings, efficiency is attained at 95% under typical test settings and at 96% when the weather is unpredictable and there are changes in temperature and irradiance.